Cardiomyopathy Associated With Tertiary Adrenal Insufficiency Manifesting as Refractory Heart Failure, Shock, and Sudden Cardiac Death: A Case Report - Wang, Xuefeng; Luo, Yong; Feng, Jian (Frontiers in Cardiovascular Medicine, 2021)
Dilated cardiomyopathy is an etiologically heterogeneous disorder. Early diagnosis and prompt treatment of the underlying disease are of great significance. Primary and secondary adrenal insufficiency are considered quite rare causes of dilated cardiomyopathy. However, to the best of our knowledge, no case of cardiomyopathy associated with tertiary adrenal insufficiency has been reported. Herein, we described a 68-year-old woman with a 15-year history of seasonal dermatitis presented with frequent heart failure and shock. At first, she was diagnosed with idiopathic dilated cardiomyopathy, but standard heart failure and antishock treatment failed. Given her long-term use of dexamethasone for treating seasonal dermatitis, and clinical manifestations consistent with adrenal insufficiency, we tested her basal plasma cortisol, simultaneous corticotropin, and other pituitary hormones, confirming that she had tertiary adrenal insufficiency. Additionally, abdominal enhanced computed tomography revealed atrophic bilateral adrenal glands, indicating long-standing and severe adrenal insufficiency. Then hydrocortisone replacement therapy was initiated, and she recovered rapidly. During the next 2 years of follow-up, she never experienced any episodes of heart failure and shock. Unfortunately, she refused the implantation of defibrillator with cardiac resynchronization therapy (CRT-D) and died of sudden cardiac death 2 years later. Although we could not exclude the coincidence of idiopathic dilated cardiomyopathy with tertiary adrenal insufficiency with 100% certainty, her unique clinical course strongly indicated that her cardiomyopathy resulted from tertiary adrenal insufficiency. This case demonstrates that patients on corticosteroids are at risk for tertiary adrenal insufficiency, which may result in refractory cardiomyopathy and even sudden cardiac death.